Pelaksanaan pembelajaran menggunakan model problem based learning pada mata pelajaran Bahasa Indonesia kelas IV SD - Lisa Dwi Rahmawati (ARKA INSTITUTE, 2022)
This research is motivated by low learning outcomes, especially Indonesian language subjects in low poetry writing material, as evidenced by the results of PISA 2017 which show that learning outcomes in Indonesia are still low on the assessment conducted by PISA. PISA data shows that Indonesia is ranked 64th out of 72 countries. The purpose of this study was to determine the implementation of problem-based learning in Indonesian language learning materials for writing poetry in the fourth grade of elementary school. Researchers used a qualitative descriptive method with direct observation techniques along with interviews with a qualitative approach. Based on the results of the research and discussion, it can be concluded that the implementation of problem based learning in Indonesian language subjects is able to improve student learning outcomes in poetry writing material for grade IV elementary school.